2006
DOI: 10.1128/jb.01927-05
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Genome Sequence of the Poultry PathogenBordetella aviumwith Those ofB. bronchiseptica,B. pertussis, andB. parapertussisReveals Extensive Diversity in Surface Structures Associated with Host Interaction

Abstract: Bordetella avium is a pathogen of poultry and is phylogenetically distinct from Bordetella bronchiseptica, Bordetella pertussis, and Bordetella parapertussis, which are other species in the Bordetella genus that infect mammals. In order to understand the evolutionary relatedness of Bordetella species and further the understanding of pathogenesis, we obtained the complete genome sequence of B. avium strain 197N, a pathogenic strain that has been extensively studied. With 3,732,255 base pairs of DNA and 3,417 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 114 publications
1
80
0
5
Order By: Relevance
“…A previous report demonstrated that cultures of B. avium were consistently resistant to penicillin and cefuroxime but susceptible to mezlocillin, piperacillin, gentamicin, amikacin, and cefoperazone (6). Although B. avium has been shown to share several virulence factors with B. pertussis, B. parapertussis, and B. bronchiseptica, it does not carry genes that encode pertussis toxin or adenylate cyclase toxin (7). B. avium and B. avium-like organisms have yet-unidentifi ed virulence factors, which may contribute to their ability to cross over from an animal host to an opportunistic human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report demonstrated that cultures of B. avium were consistently resistant to penicillin and cefuroxime but susceptible to mezlocillin, piperacillin, gentamicin, amikacin, and cefoperazone (6). Although B. avium has been shown to share several virulence factors with B. pertussis, B. parapertussis, and B. bronchiseptica, it does not carry genes that encode pertussis toxin or adenylate cyclase toxin (7). B. avium and B. avium-like organisms have yet-unidentifi ed virulence factors, which may contribute to their ability to cross over from an animal host to an opportunistic human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequences of PL-5 lyases from Achromobacter xylosoxidans (Swiss-Prot F7SXN4), Bordetella avium (34), Cobetia marina (Swiss-Prot Q9ZNB7), P. aeruginosa (35), and Spingomonas sp. A1 (PDB 1QAZ) (36) were aligned with Smlt1473 using COBALT (37).…”
Section: Electrospray Ionization Mass Spectrometry (Esi-ms) Ofmentioning
confidence: 99%
“…Comparing the genomic sequence of B. avium and other Bordetella species, Sebaihia et al (2006) described that the gene encoding the dermonecrotic toxin (dnt) is present in the B. avium genome but at a different location than in those of the previously sequenced species. The morphological changes observed in this study were very similar to the changes observed by Ohnishi et al (2008) who evaluated B. pertussis strains, yet new in vitro and in vivo studies are required to characterize the action of the toxins produced by the B. avium strains isolated from cockatiels.…”
Section: Discussionmentioning
confidence: 99%